Post-exposure prophylaxis after non-occupational exposure to HIV in Greece - Konte, V.; Pylli, Magda; Paraskeva, Dimitra; Tsiara, Chrissa; Makri, Efraxia; Raftopoulos, Vasilios; Nikolopoulos, Georgios K. (My University, 2008)
Aim: To assess the use of post-exposure prophylaxis after a non-occupational exposure to HIV in Greece. Methods: We analysed the data that were reported to the Hellenic Centre for Disease Control and Prevention by physicians who requested non-occupational post-exposure to HIV prophylaxis (NONOPEP) . Results: During the period January 1996–June 2005 inclusive, 159 persons received NONOPEP (116 males, 42 females and 1 unknown). Fifty-three per cent of the males sought NONOPEP because of an exposure to sperm and vaginal secretions, while 35.7% of the females were exposed to sperm. Unprotected sex was the main reported cause of exposure to HIV (38.36%) followed by condom rupture (35.85%). For 110 (69.18%) persons, it was the first time they were prescribed NONOPEP. Conclusion: The current surveillance system in Greece should be further developed to include the documentation of potential drug-toxicity, side effects and adherence to the prophylaxis. The health educational role of the nurse in HIV prevention in Greece should be developed.
Keywords: HIV Prevention; HIV Prophylaxis; Non-Occupational Exposure; Unprotected Sex